Funding for Social Enterprises from The European Union - Kaneva, Aglika (Research Papers, 2025)
This paper is devoted to the European Union funding opportunities for social enterprises. The European Union programs and funds that provide financial resources for social enterprises during the 2014 – 2020 period have been listed. The absorption of the European Union resources for social enterprises in Bulgaria during the period 2014 – 2020 has been analyzed. The European funds and programmes in the period 2021 – 2027 from which social entrepreneurs can receive funding have been enumerated. Funding opportunities for social enterprises under the European Social Fund Plus, The European Single Market Programme and Erasmus+ programme have been studied.
Keywords: Social enterprises; European Union funding; European social fund plus; Erasmus+ programme; European regional development fund